ASSOCIATION DEVELOPMENT OF TRICHODECTOSIS AND HELMINTHOSES IN THE DIGESTIVE TRACT OF DOGS - Mykhailiutenko, S.; Zamaziy, A.; Korchan, L. (Scientific Progress & Innovations, 2020)
Trichodectosis caused by dog-biting lice of Trichodectes canis species is one of widespread dog skin dis-eases of parasitic etiology. The infection is accompanied by itching, dermatites, and losing weight of ani-mals. At the same time, this ectoparasitosis can be complicated with helminthic diseases, which are the ob-ject of peculiar attention of specialists in both veterinary and human medicine. That is why conducting moni-toring studies and specific measures of control over epizootological situation as to dog parasitoses will in-crease in the prospect the effectiveness of the developed system of measures to fight invasion diseases of small domestic animals. The aim of the research was to establish peculiarities of association development of trichodectosis and helminthoses of domestic dogs’ digestive tract. According to the results of conducted par-asitological studies, it has been revealed that trichodectosis develops mainly in association invasions togeth-er with digestive tract helminthoses (63.16 %). Trichodectosis mono-invasion was detected in 36.84 % of infected animals. Nematodes of Trichuris vulpis, Тохоса canis, Dipylidium caninum, Uncinaria stenocephala species turned out to be associations of trichodectosis causative agent. Association development of tricho-dectosis is characterized by simultaneous presence of two, three, and four species of parasites. Moreover, two-component invasion is dominant (60.78 % of dogs diseased with trichodectosis). Three-component (33.34 %) and four-component invasions (5.88 %) were found less frequently. Trichodectosis-dipilidiosis (prevalence of infection made 17.95 %) and trichodectosis-trichurosis (10.26%) two-component invasions were registered most frequently, while trichodectosis-toxocarosis (7.68 %) and trichodectosis-uncinariosis (3.85 %) invasions were found less often. Of three-component invasions, trichodectosis-dipilidiosis-trichurosis (prevalence of infection made 8.97 %) and trichodectosis-dipilidiosis-toxocarosis (5.14 %) pre-vailed. At the same time, trichodectosis-dipilidiosis-uncinariosis, trichodectosis-trichurosis-toxocarosis, and trichodectosis-trichurosis-uncinariosis invasions were detected in 1.28-3.84 % of infected dogs. Four-component associations were presented by only two invasions, in which their prevalence of infection varied from 1.28 to 2.56 %.